Α contribution to Lasioderma spp. and other coleoptera collected from thistles in Southern Greece - Buchelos, C. ΤΗ. (ENTOMOLOGIA HELLENICA, 1989)
Coleoptera adults belonging to at least 64 species were collected in a 2-year survey held in 5 regions of southeastern Greece on different plants, members of the subfamily Cynaroideae: Compositae, commonly known as thistles. In the cited list is depicted the presence of each species according to its host, the plant part of the host, the season and the region it was collected. Species which are considered to be stored product insects are noticed while a special reference is made to Lasioderma spp. found on thistles.